An Ultrasensitive "On-Off-On" Photoelectrochemical Thrombin Aptasensor Based on Perylene Tetracarboxylic Acid/Gold Nanoparticles/Cadmium Sulfide Quantum Dots Amplified Matrix. Issue 14 (1st January 2018) - Mo, Fangjing; Han, Qian; Song, Jinyi; Wu, Jingling; Ran, Peiyao; Fu, Yingzi
Abstract : A simple "on-off-on" photoelectrochemical (PEC) thrombin (TB) aptasensor has been constructed with the assistant of the elaborately designed matrix prepared by 3, 4, 9, 10-perylene tetracarboxylic acid (PTCA), gold nanoparticles (Au NPs) and cadmium sulfide quantum dots (CdS QDs). PTCA, Au NPs and CdS QDs are used as the photoactive material, photosensitizer, and postpositive photoelectric material respectively. The preparation process of the matrix was characterized via photoelectrochemical and electrochemical technologies. The dynamic concentration monitor of TB via PEC. The results show that the sensitive TB detection can be observed on the proposed "on-off-on" aptasensor with a linear range from 1.0 × 10 −6 to 1.0 × 10 −14 mol·L −1 and the detection limit of 3.3 fmol·L −1 . Through the synergistic effect of the matrix, the obtained signal intensity is 1.6-fold higher than the initial one. The aptasensor also possesses high selectivity to the target TB over other interfering proteins or amino acid, it can be employed to detect TB in human serum samples. This approach reveals a promising avenue for increasing photocurrent efficiently by bringing in postpositive photoelectric material.